A self-locking loop as an alternative to purse-string suture in colon anastomosis - Maxon, Oskar (2016)
Colorectal cancer is among the most common and most deadly cancer types in man. Surgical removal of the tumour is the treatment of choice. Anastomotic leakage is a common and feared complication to this procedure associated with further complications and increased mortality. The exact mechanisms and risk factors of anastomotic leakage have yet to be completely understood. Alternative techniques to anastomose colon are currently investigated, aimed to develop safer and easier methods with reduced risk of complications. Intraluminal stapling or manual suturing are the conventionally used methods of anastomosis. Adaptive Anaerobic Anastomosis is a new method for anastomosis of the colon that is currently under development. The methodology is in principal based on two ring-shaped implants that lock the two intestinal ends together while the lumen remains open and allows passage of intestinal content. As the colon heals the locking rings will eventually detach and pass through the rectum. In Adaptive Anaerobic Anastomosis and intraluminal stapling, the colon lumen is temporarily sealed around the anvil shaft of the device using a purse-string suture. The aim of this study was to evaluate the feasibility of replacing the purse-string suture for closure of the colon, using a short-time implant in the form of a flexible self-locking loop, mainly in conjunction with the Adaptive Anaerobic Anastomosis method. The self-locking loop was tested in vitro on pig intestines (n=10) and in vivo in ten pigs anastomosed using either Adaptive Anaerobic Anastomosis or intraluminal stapling. The self-locking device could close the lumen around the Adaptive Anaerobic Anastomosis and stapler instruments. Subjectively, the device achieved a good tissue grip and a tight closure of the colon. The technology was perceived as easy to use and potentially time saving. This study suggested that the self-locking device may be an alternative to stapler or purse-string suture for the temporary closure of the colon in colon anastomosis. Additionally, possible improvements of the design of the self-locking loop were suggested.